Do luto à luta: a emergência do corpo deficiente possível - MIRANDA, Rosalba Martins (Universidade Federal do Pará, 2017)
This dissertative study proposes to discuss, in Foucaultian Philosophy and Difference Thinking in Education, the perspective of a possible handicapped body thought as threshold of a new political body. It problematises the paradigm of handicapped body’s inclusion, describing and tensing the historical trajectory of studies about the handicapped body in its relation/conflict with normality, having as intersection points the foucaultian genealogy and the difference studies in educational field. In the theoretical-methodological construction it searches aids in the thinking of Michel Foucault, Erving Goffman, Carlos Skliar, Jorge Larrosa, in legal documents that deals with handicapped rights, as well as analysis of testimonials from people (handicapped and handicapped’s mothers) that contributed with their life stories. In this perspective, a bibliographical research has been developed, with the purpose of diving in the complexity of the relation with the handicapped “other”, using as theoretical-methodological procedure the notions of archeology and genealogy in Foucault, articulately to the fields of moral and aesthetical problematization of the handicapped body. Among the points of discussion, stands the questioning that nowadays one lives an education in support of the inclusion paradigm, without, however, problematizing untouched aspects in this territory under other’s government. The text moves itself through three interconnected dimensions: the “mourning” (interdiction) of the handicapped body in the intricacies of historical normality, the “fight” (resistences) for legal achievements in the educational setting and of the “ethical-aesthetic” (difference) of the possible handicapped body, a body that in Larrosa’s vision “goes from the impossible to the truthful”, being the vector of its own aesthetic experience, a moral inquisitor body, capable of reinventing itself and of recreating new settings of difference in education.